Research on the Mechanical Properties and NMR Characteristics of Cement Mortar during Freeze-Thaw Cycles - Gao, Feng; Zhou, Keping; Wang, Yunmin; Liu, Taoying; Xie, Shenghua (Advances in Civil Engineering, 2019)
Low-field nuclear magnetic resonance (NMR) technology has the characteristics of nondestructive, rapid, and accurate. In the present paper, the mechanical properties and the size and distribution of pores of cement mortar during freeze-thaw cycles were studied by using the NMR technology for the first time. The change law of surface and quality, compressive strength, splitting tensile strength, and elastic modulus of cement mortar under 0, 25, 50, 75, and 100 freeze-thaw cycles were studied. And the changes of T2 spectra of cement mortar under different freeze-thaw environments were analyzed; the change rule between freeze-thaw cycles and the size of the pore within the cement mortar were also obtained. Moreover, the relationship between the mechanical properties and the pore structure of cement mortar was studied.